Acacetin inhibits inflammation by blocking MAPK/NF-κB pathways and NLRP3 inflammasome activation - Bu, Juan; Mahan, Yeledan; Zhang, Shengnan; Wu, Xuanxia; Zhang, Xiaoling; Zhou, Ling; Zhang, Yanmin (Frontiers in Pharmacology, 2024)
Objective: Our preliminary research indicates that acacetin modulates the nucleotide-binding oligomerization domain (NOD)-like receptor pyrin domain containing 3 (NLRP3) inflammasome, providing protection against Alzheimer's Disease (AD) and cerebral ischemic reperfusion injury. The mechanisms of acacetin to inhibit the activation of the NLRP3 inflammasome remain fully elucidated. This study aims to investigate the effects and potential mechanisms of acacetin on various agonists induced NLRP3 inflammasome activation. Methods: A model for the NLRP3 inflammasome activation was established in mouse bone marrow-derived macrophages (BMDMs) using Monosodium Urate (MSU), Nigericin, Adenosine Triphosphate (ATP), and Pam3CSK4, separately. Western blot analysis was employed to detect Pro-caspase-1, Pro-Interleukin-1β (Pro-IL-1β) in cell lysates, and caspase-1, IL-1β in supernatants. Enzyme-Linked Immunosorbent Assay (ELISA) measured the release of IL-1β, IL-18, and Tumor Necrosis Factor-alpha (TNF-α) in cell supernatants to assess the impact of acacetin on NLRP3 inflammasome activation. The lactate dehydrogenase (LDH) release was also assessed. The Nuclear Factor Kappa B (NF-κB) and Mitogen-Activated Protein Kinase (MAPK) signaling pathways were evaluated, including NF-κB nuclear translocation observed via laser scanning confocal microscopy (LSCM). Disuccinimidyl Suberate (DSS) cross-linking was employed to detect oligomerization of Apoptosis-associated Speck-like protein containing a Caspase Recruitment Domain (ASC), and LSCM was used to observe Reactive Oxygen Species (ROS) production. Inductively Coupled Plasma (ICP) and N-(6-methoxyquinolyl) acetoethyl ester (MQAE) assays determined the effects of acacetin on the efflux of potassium (K+) and chloride (Cl-) ions. Results: Acacetin inhibited NLRP3 inflammasome activation induced by various agonists, reducing the release of TNF-α, IL-1β, IL-18, and LDH. It suppressed the expression of Lipopolysaccharides (LPS)-activated Phosphorylated ERK (P-ERK), Phospho-JNK (p-JNK), and Phospho-p38 (p-p38), inhibited NF-κB p65 phosphorylation and nuclear translocation, and reduced ROS production. Acacetin also inhibited ASC aggregation, thus suppressing NLRP3 inflammasome activation. Notably, acacetin did not affect K+ and Cl- ions efflux during the activation process. Conclusion: Acacetin shows inhibitory effects on both the priming and assembly processes of the NLRP3 inflammasome, positioning it as a promising new candidate for the treatment of NLRP3 inflammasome-related diseases.